2016
DOI: 10.1002/jbmr.2993
|View full text |Cite|
|
Sign up to set email alerts
|

DDR2–CYR61–MMP1 Signaling Pathway Promotes Bone Erosion in Rheumatoid Arthritis Through Regulating Migration and Invasion of Fibroblast-Like Synoviocytes

Abstract: Regulation of matrix metalloproteinases (MMPs) by collagen in the fibroblast-like synoviocytes (FLSs) plays a critical role in joint destruction in rheumatoid arthritis (RA). Our previous study indicated that discoidin receptor 2 (DDR2) mediated collagen upregulation of MMPs. However, the precise underlying mechanism remains unclear. We report here that CYR61, a secreted, extracellular matrix-associated signaling protein which is capable of regulating a broad range of cellular activities, including cell adhesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…Although we failed to link CYR61 to synovial vascularization in the present study, CYR61 correlated with disease duration and increased CYR61 levels were observed in patients with high disease activity, bone erosions and HAQ>1.5. These findings are consistent with the implication of CYR61 signaling pathway in the development of bone erosion recently described, and the evaluation of CYR61 as a biomarker of structural progression in RA should be further considered [ 46 ].…”
Section: Discussionsupporting
confidence: 88%
“…Although we failed to link CYR61 to synovial vascularization in the present study, CYR61 correlated with disease duration and increased CYR61 levels were observed in patients with high disease activity, bone erosions and HAQ>1.5. These findings are consistent with the implication of CYR61 signaling pathway in the development of bone erosion recently described, and the evaluation of CYR61 as a biomarker of structural progression in RA should be further considered [ 46 ].…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, plenty of activated signaling pathways promote the secretion of inflammatory factors and aggravated immune response [ 18 , 19 ]. Particularly, regulators of extracellular matrix (ECM), such as MMPs [ 20 , 21 ], which enhanced the invasiveness of FLSs, are regarded as the “killer” of joint destruction. However, the activity of MMPs is controlled by TIMPs.…”
Section: Discussionmentioning
confidence: 99%
“…Fibroblasts may suppress the inflammatory response, and may be considered as a novel target for the therapy of inflammation. Huang et al ( 21 ) demonstrated that CCN1/Cyr61 markedly facilitates rheumatoid arthritis (RA) fibroblast-like synoviocyte invasion and migration and may act as a promising therapeutic target for RA treatment. Wei et al ( 22 ) suggested that CCN1/Cyr61 expression is significantly associated with the metastasis of gastric cardia adenocarcinoma (GCA).…”
Section: Ccn1/cyr61 Biological Functionsmentioning
confidence: 99%
“…The overexpression of CCN1/Cyr61 activates the nuclear factor (NF)-κB pathway and induces hepatic stellate cell apoptosis through endoplasmic reticulum stress and initiation of the unfolded protein response ( 23 ). Conversely, CCN1/Cyr61 expression promotes kidney tubular epithelial cell proliferation and cell apoptosis is inhibited ( 21 ). The functions of CCN1/Cyr61 in promoting cell survival or inducing apoptosis in different cell-types is important to elucidate its role in tissue reconstruction.…”
Section: Ccn1/cyr61 Biological Functionsmentioning
confidence: 99%